2018
DOI: 10.5812/iji.57914
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescription Pattern in Surgical Wards of MGM Hospital, Kamothe

Abstract: Background: Surgical antimicrobial prophylaxis refers to a brief course of antibiotic given just before surgery. Surgical site infection increases the hospital stay and prophylaxis has the potential to shorten hospital stay and fasten return to normal activity after discharge from the hospital. Therefore, the present study was undertaken to observe and analyse antimicrobial prescription pattern in patients that had undergone surgery at a tertiary care hospital. Methods: This was a prospective case series study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…Aminoglycosides and penicllins were the second and third most frequently prescribed prophylactic antibiotics owing to their broad-spectrum of activity, in particular selectivity for Gram-ve bacteria. Our results are parallel to previous studies which reported a higher prescription and use of third generation of cephalosporins [17,27,28]. On the contrary, few studies reported high prescription of penicillins, amikacin, metronidazole over cephalosporins [22,27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Aminoglycosides and penicllins were the second and third most frequently prescribed prophylactic antibiotics owing to their broad-spectrum of activity, in particular selectivity for Gram-ve bacteria. Our results are parallel to previous studies which reported a higher prescription and use of third generation of cephalosporins [17,27,28]. On the contrary, few studies reported high prescription of penicillins, amikacin, metronidazole over cephalosporins [22,27].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are parallel to previous studies which reported a higher prescription and use of third generation of cephalosporins [17,27,28]. On the contrary, few studies reported high prescription of penicillins, amikacin, metronidazole over cephalosporins [22,27]. The disparities in antibiotic selection depends on the type and nature of surgery and local antibiotic policy while some surgeons are accustomed to follow their own protocol, which has always 'worked' for them [6,16].…”
Section: Discussionsupporting
confidence: 86%
“…Sane et al [2] stated that in surgical wards, the percentages of antibiotics used for these surgeries were cefotaxime 44%, amikacin 88%, ceftriaxone 52%, metronidazole 30%, and cefixime 54%. Herawati et al [18] reported that in the Surgery Department of Bangil Regional General Hospital, Pasuruan, the 3 most-used antibiotics are ciprofloxacin (11.8 DDD / 100 patient-days), ceftazidime (6.7 DDD / 100 patient-days), and cefixime (4.3 DDD / 100 patient-days).…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics are substances, which are obtained from one microorganism and prove fatal for other microorganism at low concentration and can be either a bactericidal or bacteriostatic agents [2]. Surgical patients are in general high consumers of antibiotics [3].…”
Section: Introductionmentioning
confidence: 99%
“…27 Third generation cephalosporins were the preferred antibiotics for pre-operative use as well as for the use in combination with aminoglycoside and metronidazole for better postoperative antibiotic coverage. 28 ASA score was significantly associated with SSI development. Results suggest that patients with severe systemic disease (ASA classes III and IV) run a higher risk of SSI than patients with mild or no systemic disease, as supported by previous research.…”
Section: Discussionmentioning
confidence: 95%